"It Is Her Body, Silent/ and Fingerless, Writing this Poem": Margaret Atwood's Notes Towards a Poem That Can Never Be Written - Hoofard, Jennifer M. (Atlantis, 2006)
This article considers Margaret Atwood's Notes Towards A Poem That Can Never Be Written, poems concerned with torture as a human rights violation. It weighs Atwood's appropriation of the suffering of a colonized subject position, with the ethical imperative not to be silent, and hence complicit with existing regimes of power.